Cenzurowanie „Pamiętnika Literackiego” przed i w czasie stanu wojennego (1980–1983) - Budrowska, Kamila (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article discusses the censorship of the magazine “Pamiętnik Literacki” (Literary diary) between 1980 and 1983. The investigation is based on selected archive materials from the Central Control Office of the Press, Publications and Public Performances and on the analysis of the content of individual volumes of the magazine. The research shows that the censorship editing within this period reflects the speed and violence of the political changes under martial law and in the months directly preceding its introduction. Based on the changes regarding “Pamiętnik Literacki”, the author managed to track and confirm both the partial lifting of the restrictions imposed by the institutional control during the so-called “carnival” of the Solidarity movement (August 1980–December 13, 1981), and the introduction of the repressive “wartime” censorship, gradually eased until the lifting of martial law. The theme most thoroughly investigated by the censorship office, and the gauge of the level of censorship, was Czesław Miłosz and his writings, since he was banned from being published in the Polish People’s Republic for almost thirty years.